4-methylumbelliferone induces senescence, inhibits migration and modulates CD44 as well as RHAMM in human glioblastoma cell lines - Poodts, Daniela (2019)
4-methylumbelliferone (4MU) is a non-toxic coumarin derivative used as inhibitor of hyaluronan (HA) synthesis, but there are reports about independent effects of this inhibition. Currently, this drug is being studied on several neoplasms. Nevertheless, little is known about its effects on glioblastoma (GBM), the most frequent and malignant primary tumor of the central nervous system. HA is strongly involved in tumor progression, favoring cell proliferation and migration through its main receptors, CD44 and RHAMM, both associated with poor prognosis. GBM shows higher levels of HA than normal brain tissue. Given that current therapy for this tumor is ineffective and highly toxic, new drugs are needed for GBM treatment. Our hypothesis is that 4MU is a potential new drug for GBM therapy. Therefore, the aim of this work was to evaluate the effects of 4MU on cell proliferation, migration, senescence induction, expression of CD44 and RHAMM, and the receptors involved in HA-induced migration on LN229 and U251 human GBM cell lines. Cell proliferation was evaluated by BrdU incorporation assay, migration by the wound healing assay, senescence by SA-β-gal assay and expression of receptors by Western Blot (WB) and immunofluorescence (IF). We found that 4MU inhibited cell proliferation and migration in a dose-dependent manner in both cell lines (p<0.05). These effects were not prevented by the co-treatment with HA. Besides, 4MU increased the percentage of SA-β-gal+ cells in a dose-dependent manner in U251 cell line, but in LN229 cells only at the higher dose (p<0.05). Furthermore, 4MU modulates the expression of RHAMM and CD44 (p<0.05). Regarding the implication of CD44 and RHAMM in HA-induced migration, we evaluated this process using blocking antibodies which prevented the effect of HA (p<0.05). In conclusion, we demonstrated that 4MU inhibited all studied processes involved in GBM malignancy, thus being a promising therapy for GBM.